Modeling the Impact of the Green Roofs as a Nature-Based Solution to Mitigate the Urban Heat Island Effects over Attica, Greece - Kalogeri, Christina; Spyrou, Christos; Koukoula, Marika; Saviolakis, Pantelis M.; Pappa, Aikaterini; Loupis, Michael; Masouras, Charis; Katsafados, Petros (Environmental Sciences Proceedings, 2023)
The main aim of this study is to model the Nature-based solution of Green Roofs (GRs) in order to assess their efficiency as a mitigation strategy for UHI effects and extreme summertime temperatures over Attica in Greece. The area of study is a region that encompasses Athens, the largest Metropolitan area of Greece, and the suburbs. The analysis has been performed with the use of an advanced modeling system that consists of the mesoscale Weather Research and Forecasting model (WRF) and the advanced multilayer urban canopy scheme building energy parameter and building energy model (BEP/BEM). The two modules are fully coupled, forming WRF urban. For a better description of the urban environment and in order to use the full capabilities of the urban canopy scheme, 11 urban classes corresponding to the WUDAPT Local Climate Zones (LCZ) were used instead of the 3 traditional urban classes that the default version uses. Sensitivity tests for a major heatwave that affected the area of study have been performed in order to evaluate the impact of GRs on the UHI structure. Results indicate that the modification of the roof energy budget decreased the maximum temperature during heatwaves and altered the spatio-temporal pattern of the effect.